PERANCANGAN UI/UX APLIKASI SCHOOL CONTROL HUB LAYANAN INFORMASI ABSENSI SISWA MENGGUNAKAN APLIKASI FIGMA - Uswa, Ade; Suwartika, Rini (POLITEKNIK PIKSI GANESHA, 2024)
The student attendance information service is a system designed to process and present student attendance data. The School Control Hub application is an attendance information service designed to facilitate the management of student attendance data by the school and provide easier access for parents to monitor their children's attendance. In this design, Figma was used as the primary tool to design and implement the UI/UX concept. The prototype design of the School Control Hub application demonstrates that the developed UI/UX design is able to meet users' needs effectively. Therefore, the School Control Hub application is expected to be an effective solution for managing student attendance that is easily accessible for obtaining attendance information.